A dawning understanding of enactment and sado-masochistic interaction - a child analysis of a latency child. Issue 1 (2nd January 2020) - Kamphus, Henrik
ABSTRACT: The paper seeks to describe how a sado-masochistic dynamic for a long period of time characterized the relationship between the analyst and the analysand. But after a dawning reflective understanding that the analytic relationship was filled with sado-masochistic quality he succeeded better in liberating himself from a destructive pathological dynamic and reclaim an analytic attitude. The discussion of the clinical material consists of mainly three parts: The sadomasochistic relationship gives a picture of the power-struggle in the patient´s general way of relating. The understanding of enactment shows how this is played out in the relationship with the analyst, and technically how analyst-centred-interpretations can be a tool in addressing this difficult and emotional straining work. The author also claims that there is a natural connection between these constructs in analysis with children taken into account that children are emotionally more immature with a tendency to acting out and to a greater degree need the emotionally containing- and affirmative basis of analyst-centred interpretations that exemplifies the need of a containing analyst with an alpha-function.